Supporting Factors and Barriers to Implementing the Referral System in Primary Health Care - Laode Ardini; Elly L. Sjattar; Erfina Erfina (Jurnal Keperawatan Silampari, 2023)
This study aims to identify the supporting and inhibiting factors for the implementation of the referral system in primary health care. This study used a scoping review design, using four databases namely PubMed, ProQuest, ScienceDirect, and Garuda, using keywords based on the PCC method (Population, Concept, Contect. The results of this study identify a number of supporting and inhibiting factors for the implementation of the referral system in primary health care, showing that the supporting factors are human resources, facilities and infrastructure, medicines, medical devices, referral fees, referral information and support from various parties. While the inhibiting factors are knowledge/understanding of officers or patients, accessibility, SOP/regulation of referrals, information systems, completeness of the referral process and social culture of the community. In conclusion, with several supporting and inhibiting factors in the implementation of the referral system in primary health care identified, causing referral health services to not be optimal. Keywords: Supporting Factors, Barriers, Primary Health Care, Referral Systems